Mothers' experiences of a telephone based breastfeeding support intervention after discharge from neonatal intensive care units: a mixed-method study - Jenny Ericson; Renée Flacking; Camilla Udo (BMC, 2017)
Abstract Background After discharge from a neonatal intensive care unit (NICU), many mothers of preterm infants (gestational age < 37 weeks) experience a lack of support for breastfeeding. An intervention study was designed to evaluate the effects of proactive (a daily telephone call initiated by a member of a breastfeeding support team) and/or reactive (mothers could call the breastfeeding support team) telephone based breastfeeding support for mothers after discharge from the NICU. The mothers in the intervention group had access to both proactive and reactive support; the mothers in the control group only had access to reactive support. The aim of this study was to explore the mothers' experiences of the proactive and reactive telephone support. Methods This study was a qualitatively driven, mixed-method evaluation using three data sources: questionnaires with qualitative open-ended questions, visual analogue scales and telephone interviews. In total, 365 mothers contributed data for this study. The qualitative data were analysed with an inductive thematic network analysis, while the quantitative data were analysed with Student's t-test and the chi-square test. Results Proactive support contributed to greater satisfaction and involvement in breastfeeding support. The mothers who received proactive support reported that they felt strengthened, supported and secure, as a result of the continuous care provided by staff who were knowledgeable and experienced (i.e., in breastfeeding and preterm infants), which resulted in the global theme 'Empowered by proactive support'. The mothers who received reactive support experienced contradictory feelings; some felt secure because they had the opportunity to call for support, whereas others found it difficult to decide when and if they should use the service, which resulted in the global theme; 'Duality of reactive support'. Conclusion There were positive aspects of both proactive (i.e., greater satisfaction and feelings of empowerment) and reactive support (i.e., the opportunity to call for support); however, the provision of reactive support alone may be inadequate for those with the greatest need for support as they are the least likely to access it. Trial registration NCT01806480 on 5 March 2013.